Supporting research students - Allan, Barbara 1954- (Facet Publishing, 2009)
This volume offers guidance to LIS professionals to enable them to support the specialist needs of research students effectively. The key areas covered include the world of research and research students, styles of research, skills required by research students, and the rise of the virtual graduate school.